Empirical Study on the Impact of Urban Residents’ Income on Consumption Structure in Yantai City - Lei, Ding (Journal of Global Economy, Business and Finance, 2025)
In recent years, with the rapid development of Yantai’s economy, the income level of residents in Yantai has also been significantly improved. The per capita disposable income of urban residents in Yantai City has reached 45143 yuan in 2022. With the growth of urban residents’ income in Yantai City, the consumption structure of urban residents is also undergoing changes. In order to reveal the relationship and degree of the impact of income growth on consumption structure of urban residents in Yantai City, a model of income and consumption structure of urban residents in Yantai City was established by consulting the Yantai Statistical Yearbook and obtaining the required data. Empirical analysis and testing were conducted. Research shows that the expenditure of urban residents in Yantai City on food, housing, medical care, entertainment, and other aspects continues to increase with the increase of disposable income. The consumption expenditure of urban residents in Yantai City is transforming and upgrading towards spiritual consumption and development consumption. Finally, suggestions were put forward to increase the income of urban residents in Yantai and improve the consumption structure.